2018
DOI: 10.3389/fpsyg.2018.01332
|View full text |Cite
|
Sign up to set email alerts
|

Community-Dwelling People Living With Dementia and Their Family Caregivers Experience Enhanced Relationships and Feelings of Well-Being Following Therapeutic Group Singing: A Qualitative Thematic Analysis

Abstract: The progression of dementia can severely compromise interpersonal connection and relationship quality between people living with dementia (PwD) and their family caregivers (FCG), leading to social isolation and poor quality of life for both. Therapeutic group singing (TGS) is a socially engaging, stimulating, and supportive pursuit that community-dwelling PwD and their FCG can participate in together. This study aimed to build on the findings from previous research by undertaking a thematic analysis of intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(153 citation statements)
references
References 34 publications
7
146
0
Order By: Relevance
“…Results of the full thematic analysis of the qualitative interview data is published elsewhere ( 36 ). For the feasibility investigation, which is the purpose of the current paper, we will explore the qualitative results that pertain to the participants' experience of the Remini-Sing therapeutic singing group intervention, of participating in research and their experience of completing the quantitative measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the full thematic analysis of the qualitative interview data is published elsewhere ( 36 ). For the feasibility investigation, which is the purpose of the current paper, we will explore the qualitative results that pertain to the participants' experience of the Remini-Sing therapeutic singing group intervention, of participating in research and their experience of completing the quantitative measures.…”
Section: Resultsmentioning
confidence: 99%
“…Although we had intentionally attempted to look at the positive aspects of caregiving, rather than caregiver burden, based on the participant experience of the PACQ, we would choose to examine caregiver burden in a future study. Further, one of the major themes that emerged from our full qualitative analysis ( 36 ) was the effect of the group singing intervention on building new supportive relationships. Therefore, we would also include a measure of social connectedness in future studies in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interview responses from participants in Studies 2 and 3 emphasized these findings, with frequent mentions of connecting with others, sharing personal struggles and triumphs, and feeling joy as a result of this bonding process. These social experiences are often reported in other studies of artistic interventions (Baker et al, 2018;Clark et al, 2018;Dingle et al, 2013) and it is postulated that they help promote the positive health outcomes that are also observed among study participants (Ronzi, Orton, Pope, Valtorta, & Bruce, 2018). This was especially evident in Study 6, when social identification was measured for each group membership reported by participants.…”
Section: The Role Of Social Identitysupporting
confidence: 52%
“…During this time, it is also important to involve caregivers if applicable, as they too can benefit from interactive, artistic programming. Indeed, social interventions can also provide caregivers with the opportunity to bond with their care recipient and to share their struggles with other carers (Baker et al, 2018;Clark et al, 2018;Dassa et al, 2018). As was observed during the reminiscence and music-making studies, caregivers enjoyed bonding with their care recipient through program activities.…”
Section: Considerations For Future Interventionsmentioning
confidence: 91%